NPM1 and FLT3 mutations in acute myeloid leukemia with normal karyotype: Indian perspective - Sudha Sazawal; Neha Singh; Sonal Jain; Sunita Chhikara; Rekha Chaubey; Jina Bhattacharyya; Kandarpa Kr Saikia; Manoranjan Mahapatra; Renu Saxena (Wolters Kluwer Medknow Publications, 2017)
Background: FLT3-ITD and NPM1 mutations are considered to be the major determinants of the patient response to therapy and outcome. The primary aim of this study was to establish the correlation between these molecular mutations and the clinico-hematologic parameters as well as the prognostic outcome of the Indian acute myeloid leukemia (AML) patients. Materials and Methods: This prospective study involved newly diagnosed nonpromyelocytic AML patients who had undergone complete diagnostic workup, including immunophenotyping, conventional cytogenetics and molecular analysis for NPM1 and FLT3-ITD mutation by reverse transcriptase polymerase chain reaction at presentation. Results: Overall, the prevalence of NPM1 and FLT3-ITD mutations was found to be 14.4% and 10.8%, respectively. Among patients with normal karyotype, leukocytosis was significantly associated with NPM1+ group than the NPM1− group (P = 0.0019) and more severe degree of anemia was observed in the FLT3-ITD+ patients than the other groups (P = 0.025). No significant correlation was found in terms of age at presentation (P = 0.56), sex ratio (P = 0.467), median platelet count (P = 0.27), and blast percentage between NPM1+ and FLT3-ITD+ groups. Complete remission (CR) rates were better in the NPM1+/FLT3-ITD− group than the other three groups. Unlike most other studies, improved CR rates as well as disease-free survival were observed in the NPM−/FLT3-ITD− group than the FLT3-ITD+ groups although not reaching statistically significant levels. Conclusion: Some differences in the clinical behavior of the Indian AML patients in comparison to that of the West in the presence of NPM1 and FLT3-ITD suggests that comprehensive studies are required to confirm the definitive role of these mutations among AML patients, especially with normal karyotype.